Repeal of the Rent Control Act and its impacts on the pre-war shophouses in George Town, Malaysia - Mohit, Mohammad Abdul; Sulaiman, Mohd Bashir (2006)
Pre-war buildings including the shophouses constitute an important element in the urban fabric of Malaysian cities. Being located within the traditional commercial areas, these buildings not only adorn the streetscape but support urban living and socio-economic activities. The Control of Rent Act 1966 (Act 56), enforced on 1 January 1967 by the Government of Malaysia, by default contributed to the heritage conservation in Malaysia. However, the Malaysian Government repealed the Act in 1997. The repeal of the Act adversely affected the historic buildings in the country. This paper studies the impacts of the repeal of the Control of Rent Act on the rent and property markets of pre-war buildings in general and the extent of renovation of the shophouses in particular in Noordin Street in Georgetown, Penang.